Effects of Participation in Support Groups on Alzheimer's Family Caregivers' Strain and Spiritual Wellbeing - Farahnaz Mohammadi; Mehrzad Babaee (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: Since support for family caregivers is crucial in providing care for elderly, this study was conducted to examine the effects of participation in support groups on Alzheimer’s family caregivers’ strain and spiritual wellbeing. Materials and Methods & Materials: In this semi-experimental study, 32 accessible family caregivers of elderly patients with Alzheimer who had at least one year of experience participated. The intervention consisted of a 4-month active participation in educational and emotional supportive sessions related to patient and caregivers care management. At the end of the intervention, the leadership of the groups was transferred to members of the groups. These sessions were conducted in 3 public centers in the community. Caregivers were assessed by caregiving strain and spiritual wellbeing questionnaires at the beginning, at the end of the intervention and 2 months later. Data was analyzed by ANOVA with repeated measurement. P<0.05 was considered statistically significant. Results: In general, 32 accessible family caregivers of elderly Alzheimer patients with at least one year of experience participated in this study. The mean of spiritual wellbeing through three mentioned measurements showed an improvement (26.029, 34.029, 34.471), whereas the care giving strain showed a decreasing trend (40.118, 32.706, 31.265). Findings based on ANOVA-repeated measurement revealed a significantly decrease in care giving strain (P=0.001) and an improvement in spiritual wellbeing (P=0.005). Conclusion: Participation in the support groups as a manifest of empowering helps family caregivers to deal effectively with care giving difficulties. Psychoeducational programs lead to a decreased care giving strain and improve the spiritual wellbeing of the caregivers. Hence, supportive interventions should be considered by policy makers and professional health care providers for elderly people.